ASSESSING CLINICAL OUTCOMES OF CASES OF BELL’S PALSY IN A TERTIARY CARE HOSPITAL - Haq, Mian Ayaz ul; Muhammad Irfan Khan; Mian Iftikhar ul Haq; Ateeq ul Alam; Saqib Ali (Journal of Postgraduate Medical Institute, 2022)
Objective: To assess the clinical outcomes of Bell’s palsy in patients presenting to a tertiary care hospital Methodology: The descriptive study was conducted at the Department of Neurology, Lady Reading Hospital from 1st June 2017 to 31st July 2018 on 113 patients using non-probability purposive sampling. Patients, received at the department of neurology or referred from the department of maxillofacial surgery and neurosurgery, between 16 and 80 years of age with idiopathic unilateral facial weakness were included in the study, after taking informed consent and approval from the ethical committee. The patient data regarding the demographic details, clinical features, risk factors, and follow-up outcomes were entered into a pre-designed proforma. The data was analyzed using SPSS version 20. Results: Out of 156 patients who presented with bell’s palsy, 113 fulfilled the inclusion and exclusion criteria. Majority were females (n=58, 51.32%) and had laterality on the right side (n= 64, 56.63%). High incidence was noted in patients in the age range 16-29 years (n=51, 45.13 %). The commonest risk factor was hypertension (n=9, 7.96%). Conclusion: The common risk factors of Bell’s palsy in our setup are hypertension, diabetes, and pregnancy in chronological order. There is strong evidence of benefits from the early use of corticosteroids.